Management of Hajj Pilgrims with Disabilities During Debarkation in 2024: Case Report - Feronika, Aldona; Christyadji, Christyadji; Rachmawati, Ermin (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah MedicineDO - 10.18860/anshar.v2i0.3300, 2025)
The challenges that arise for pilgrims with special needs such as limited mobility are the increased risk of fatigue, injury, and falls. The various challenges that arise are not only caused by the pilgrims themselves, but also involve the hajj team, facilities and infrastructure, infrastructure, disability support that is still lacking, and ineffective management time, even though there are already guidelines for facilities for pilgrims with disabilities by the Ministry of Hajj Kingdom of Saudi Arabia, especially at the airport, transportation in Saudi Arabia, hotels and the Grand Mosque. The purpose of this case report is to find out the management of pilgrims with special needs, especially at the airport during the 2024 hajj disembarkation period. Case report: A 79-year-old male Indonesian pilgrim complained of weakness and shortness of breath. The pilgrim is a person with a physical disability due to a stroke who was treated at a Saudi Arabian hospital. Upon arrival at the airport, pilgrims do not get the priority they should, namely the late initial examination of sick pilgrims, officers have difficulty when conducting initial examinations at the airport due to crowds, long queues and lack of communication between officers, plus the absence of medical record data on pilgrims' care while in Saudi Arabia, health workers in Indonesia do not have sufficient information regarding the pilgrims' treatment history so that it can have an impact on the continuity of pilgrims' care, and access to transportation for pilgrims in Saudi Arabia still faces challenges in terms of being disability-friendly, because many buses are not equipped with wheelchair facilities. Management of pilgrims with special needs still faces various serious challenges, especially at the airport during the disembarkation period. Although guidelines for facilities for pilgrims with disabilities have been regulated by the Saudi Arabian Ministry of Hajj, their implementation in the field is often not optimal.